Philippines : Financial Sector Assessment Program-Detailed Assessment of Observance-Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2020)
The BSP's regulatory framework is broadly effective for the size and complexity of the Philippine banking system, but legislative gaps continue to hinder effective supervision of banks. The BSP has a well-resourced, experienced and highly committed staffing complement, but there is an ongoing need to develop and maintain adequate expertise in certain complex areas (e.g., risk modelling). Since the FSAP in 2002, and the assessment update in 2010, the BSP has made significant progress in enhancing the regulatory framework in a number of areas. But significant weaknesses in the legislative framework, arising notably from the bank secrecy laws and the lack of power for the BSP to supervise the parent companies and their affiliates of banking groups, present a material hindrance to effective supervision.